Cellulose: A Contribution for the Zero e‐Waste Challenge. Issue 7 (19th April 2021) - Nandy, Suman; Goswami, Sumita; Marques, Ana; Gaspar, Diana; Grey, Paul; Cunha, Inês; Nunes, Daniela; Pimentel, Ana; Igreja, Rui; Barquinha, Pedro; Pereira, Luís; Fortunato, Elvira; et al.
Abstract: The world in the 21st century is confronted with multifaceted challenges against rapid climate change and continuous ecological disturbances caused by revolutionary socio‐economic developments, accelerated expansion of disposable electronic gadgets, and growing dependence on unrecyclable raw materials, among others. The ever‐increasing consumer demand for electronic devices is significantly contributing to the world's fastest‐growing waste stream, known as electronic waste (e‐waste), which is becoming an environmental threat at an alarming rate due to its toxic legacy. The ever‐shortening lifespan of smart technologies has created a "tsunami of e‐waste, " as the United Nations has characterized it, with 50 million tons accumulated each year, of which only 20% undergo formal e‐recycling. Therefore, the challenge of optimizing the current resources management models with an aim of improving the manufacturing processes and lifecycles of electronic devices, as well as building a circular economy, has become significantly prominent. Paper/cellulose, which covers a wide range of essential needs in everyday scenarios (from packaging to writing utilities), constitutes promising candidates for the effective achievement of a circular economy. Particularly, cellulose is revealed as an advantageous material for electronic applications because of its abundant availability, which contributes to its cost‐effectiveness, straightforward fabrication process, and high recyclability and reproducibility. Abstract : The growing stream of electronic waste or e‐waste, that is created when an electronic product is discarded or expired, is now a big environmental concern. In that context, cellulose or paper can be a promising candidate for Green Technology while promoting zero e‐waste, because of its low‐cost, flexible, abundant, renewable, and eco‐friendly nature.